2002
DOI: 10.1046/j.1365-2672.2002.01785.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a quaternary ammonium biocide on the performance and characteristics of laboratory-scale rotating biological contactors

Abstract: Aims: To study the effect of a quaternary ammonium biocide, didecyldimethylammonium chloride (DDAC), on the treatment efficiency of laboratory-scale rotating biological contactors (RBCs) as well as their component biofilms. Methods and Results: Biofilms were established on the RBCs and then exposed to 0-160 mg l )1 (p.p.m.) DDAC at a flow rate of 2AE5 l h )1 . The treatment efficiency of the RBC and the microbial activity of the biofilms were markedly decreased when 40 mg l )1 DDAC or greater were applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…Several researchers have verified the environmental contamination by DDAC and the biodegradation of DDAC and showed that some microorganisms can degrade DDAC (Nishihara, 2000;Schoenig, 2001), but the worry remains at that higher DDAC concentrations obstruct its complete degradation. However, DDAC has the efficiency as a disinfectant against E. coil at a lower concentration than 20 mg/L which is the MIC value obtained for microorganisms in wastewater treatment system (Laopaiboon et al, 2002). Consequently, DDAC is thought to be a useful disinfectant for washing apparatuses and facilities in food factories, and in environmental sanitation.…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
“…Several researchers have verified the environmental contamination by DDAC and the biodegradation of DDAC and showed that some microorganisms can degrade DDAC (Nishihara, 2000;Schoenig, 2001), but the worry remains at that higher DDAC concentrations obstruct its complete degradation. However, DDAC has the efficiency as a disinfectant against E. coil at a lower concentration than 20 mg/L which is the MIC value obtained for microorganisms in wastewater treatment system (Laopaiboon et al, 2002). Consequently, DDAC is thought to be a useful disinfectant for washing apparatuses and facilities in food factories, and in environmental sanitation.…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
“…The configuration of the single stage laboratory scale RBC units is shown in Table 1. Laopaiboon et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…It is accepted that sessile bacteria are more resistant to a biocide than their planktonic counterparts (Eginton et al 1998;Stewart et al 1998;Laopaiboon et al 2002). However, when the bacteria in the biofilms shed to the planktonic phase, they showed no increase in resistance to the biocide.…”
Section: Susceptibility Changes Of Cells To the Bactericidal Activitymentioning
confidence: 99%
“…In addition to aerosol forms, in manmade water systems, legionellae, like most other aquatic bacteria often exist as attached complex consortia (Green and Pirrie, 1993;Murga et al, 2001;Petti et al, 2004). Biofilms and sediments might create significant problems such as fouling (Johansen et al, 1997), heat transfer resistance (Wright et al, 1991), filter plugging (Laopaiboon et al, 2002) and metal corrosion (Momba and Binda, 2002), as well as increased resistance to antimicrobial compounds (Green and Pirrie, 1993;Surman et al, 1993;Viera et al, 1999;Kool, 2002) in water systems.…”
Section: Introductionmentioning
confidence: 99%
“…QACs have been actively deployed since the 1930s with no apparent reduction in their effectiveness (McBain, 2004). These are a widely used group of non-oxidizing biocides for control of microbial growth in a variety of applications, such as cooling tower systems, disinfection and sterilisation, corrosion inhibition, wood preservation, dispersion agents and in food production (Lutey, 1995;Laopaiboon et al, 2002;Majtàn and Majtànovà, 2003;Korukoglu et al, 2006). Gemacide PN-50 TM is an alternative compound to oxidizing agents, safe for humans, stable in solution even at elevated temperatures and a wide range of pH.…”
Section: Introductionmentioning
confidence: 99%